Zhachong Shisanwei pill drug-containing serum protects H2O2-Induced PC12 cells injury by suppressing apoptosis, oxidative stress via regulating the MAPK signaling pathway - Hu, Hanqiong; Sun, Yifan; Yang, Zhen; Che, Limuge; Cai, Mingyang; Li, Xiaoxuan; Huang, Xianju; Bagen, Hurile; Qiqige, Wulan; Guleng, Wuyunsiri; Ma, Liqun; Tong, Haiying (Frontiers in Pharmacology, 2024)
Introduction: Zhachong Shisanwei Pill (ZSP) is a classical Mongolian formula that combines 13 types of Chinese medicinal materials and has been used for treating ischemic stroke (IS) for centuries. However, the underlying molecular mechanisms have yet to be fully elucidated. The aim of this study is to explore potential mechanism of ZSP on nerve cells in cerebral ischemic injury. Methods: To simulate the pathological process of oxidative stress following IS, an injury model using PC12 cells was induced with hydrogen peroxide (H2O2). Afterward, PC12 cells were treated with ZSP medicated serum at low, medium, and high doses. Various assays were conducted to assess cell viability and oxidative stress indicators, including lactate dehydrogenase (LDH), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), reactive oxygen species (ROS), and mitochondrial membrane potential (MMP). Cell apoptosis was evaluated through morphological assessment and flow cytometry. Additionally, the expression levels of apoptosis-related proteins (Bcl-2, Bax, Caspase-9, Caspase-3, PARP) and signaling pathway proteins (JNK, phosphorylated JNK, ERK, phosphorylated ERK, p38, and phosphorylated p38) were measured using automated western blotting. Results: Our findings indicate that ZSP medicated serum preconditioning improves the condition of PC12 cells injured by H2O2. Specifically, it increased cell survival rates and reduced LDH release. Additionally, ZSP treatment decreased ROS levels and MDA content, while enhancing the activity of SOD and CAT in the injured PC12 cells. ZSP also reversed the depolarization of mitochondrial membrane potential and protected cells from apoptosis by modulating the expression of apoptosis-related proteins, including Bcl-2, Bax, Caspase-9, Caspase-3, and PARP. Furthermore, the overactivation of the MAPK signaling pathway due to H2O2-induced injury was inhibited, as evidenced by the downregulation of phosphorylated JNK, ERK, and p38 levels. Discussion: Mongolian medicine ZSP demonstrates protective effects against H2O2-induced oxidative stress and apoptosis in PC12 cells. The underlying mechanism may involve the inhibition of the MAPK signaling pathway, enhancement of antioxidant enzyme activity, reduction of intracellular peroxidation levels, and suppression of intrinsic apoptosis pathways.